Typing of Campylobacter jejuni isolated from poultry on the basis of flaA-RFLP by various restriction enzymes. (December 2018) - Yadav, Rahul; Yadav, Jyotika; Maherchandani, Sunil; Kashyap, Sudhir Kumar
Abstract: RFLP analysis of the flagellin ( fla A) gene was compared using three different restriction endonucleases i.e Dde I, Hinf I and Dpn II to determine the genetic diversity among 43 Campylobacter jejuni isolates of poultry origin from the same geographical area. fla A gene was amplified in all the isolates and RFLP analysis showed variations. Dde -based RFLP was found most efficient in discriminating C. jejuni isolates by generating 15 different Dde -RFLP patterns with discriminatory index (D.I) of 0.9258 whereas Dpn II produced seven Dpn -RFLP patterns (D.I .= 0.8427). While Hinf I enzyme produced only six Hin f-RFLP patterns (D.I .= 0.6977). The discrimination of Dpn -RFLP was comparable to discrimination given by Dde -RFLP analysis, which is generally used to study fla A gene RFLP.